State of information and analytical support of scientific activities under Belarusian libraries conditions - N. M. Lutsko (Цифровая трансформация, 2017)
The article contains the analysis of the state of information and analytical support of scientific activity under conditions of the libraries of the Republic of Belarus. A general assessment of the process of information and analytical support of science is given. The main developments and projects in the field of open access to scientific and educational resources of Belarus are described.